Crowdsourcing and Public Participation to Advance Global Environmental Protection - Ghasemi, Shadi; Tayebi, Sobhan (Fakultas Hukum Universitas Lampung, 2024)
The principles of international environmental law provide a robust framework for analyzing the legal dynamics of environmental hazards. Central to this framework is the principle of participation, which is pivotal in enhancing environmental protection and mitigating the progression of environmental hazards. By leveraging methods like crowdsourcing, this principle can foster a more engaged public involvement in safeguarding the biosphere. This research explores participatory democracy, access to information, public decision-making, and environmental litigation as fundamental approaches to achieving the objectives of international environmental legislation. It aims to illuminate the two-way interaction between these elements and assess the feasibility of actualizing the participation principle through crowdsourcing. The research examines the effectiveness of crowdsourcing as a tool for implementing this principle in supporting and protecting the environment. By reviewing and analyzing relevant sources, the article posits that increasing stakeholder participation, including civil groups and individuals, can enhance the effectiveness of environmental legislation and advance social and environmental justice. It advocates for the creation of platforms that facilitate information sharing and stakeholder engagement, along with mechanisms to ensure accountability and balance power, as crucial strategies for effective environmental governance.